With the old breed : at Peleliu and Okinawa - Sledge, E. B. (Eugene Bondurant), 1923-; Hanson, Victor Davis (New York, N.Y. : Presidio Press, 2007)
Described as one of the finest memoirs to emerge from any war, this book tells with compassion and honesty of the cruelty, bravery and deaths of the men Eugene Sledge fought alongside, and of his own journey from patriotic innocence to battle-scarred veteran
Originally published: Novato, Calif. : Presidio Press, c1981.
Includes bibliographical references and index.
Keywords: Sledge, E. B. -- 1923-; United States. -- Marine Corps. -- Marines, 5th. -- Battalion, 3rd. -- Company K. -- Biography; World War, 1939-1945 -- Campaigns -- Palau -- Peleliu Island; World War, 1939-1945 -- Campaigns -- Japan -- Okinawa Island; World War, 1939-1945 -- Personal narratives, American; Soldiers -- United States -- Biography; Peleliu Island (Palau) -- History; Okinawa Island (Japan) -- History